2003
DOI: 10.1078/1439-6092-00076
|View full text |Cite
|
Sign up to set email alerts
|

Convergent evolution of aposematic coloration in Neotropical poison frogs: a molecular phylogenetic perspective

Abstract: Poison frogs of the family Dendrobatidae contain cryptic as well as brightly colored, presumably aposematic species. The prevailing phylogenetic hypothesis assumes that the aposematic taxa form a monophyletic group while the cryptic species (Colostethus sensu lato) are basal and paraphyletic. Analysis of 86 dendrobatid sequences of a fragment of the 16S rRNA gene resulted in a much more complex scenario, with several clades that contained aposematic as well as cryptic taxa. Monophyly of the aposematic taxa was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
141
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(158 citation statements)
references
References 39 publications
15
141
0
2
Order By: Relevance
“…This and a high degree of convergence led to numerous misinterpretations of anuran phylogeny which were based on morphological traits alone (e.g. Bossuyt and Milinkovitch, 2000;Chiari et al, 2004;Vences et al, 2003). Therefore, and despite important recent advances, amphibian systematics have remained poorly resolved (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This and a high degree of convergence led to numerous misinterpretations of anuran phylogeny which were based on morphological traits alone (e.g. Bossuyt and Milinkovitch, 2000;Chiari et al, 2004;Vences et al, 2003). Therefore, and despite important recent advances, amphibian systematics have remained poorly resolved (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, and despite important recent advances, amphibian systematics have remained poorly resolved (e.g. Darst and Cannatella, 2004;Faivovich et al, 2005;Frost et al, 2006;Grant et al, 2006;Graybeal, 1997;Ruvinsky and Maxson, 1996;Vences et al, 2003), and amphibian diversity seems to be still largely underestimated in terms of the number of species, and genera as well as families (e.g. Biju and Bossuyt, 2003;Borkin et al, 2004;Bossuyt et al, 2004;De la Riva et al, 2000;Meegaskumbura et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Observations of several different species of blanched and melanic animals ranging from lizards to pocket mice inhabiting the Tularosa Basin provide a dramatic example of convergent evolution over a broad taxonomic scale (Figure 3). Independent evolution of pigmentation and pattern has been observed in many vertebrate species, including poison frogs (Vences et al, 2003), orioles (Omland and Lanyon, 2000), cavefish (Strecker et al, 2003) and cichlid fish (Allender et al, 2003), and provides exciting opportunities to ask whether the same or different genes are responsible for convergent phenotypes.…”
Section: Evolution: Natural Variation In Pigmentationmentioning
confidence: 99%
“…They based use of this name on identification of the material by E. R. Dunn; thus, these records should not be considered further. Vences et al (2003) found molecular differences between D. galactonotus and other large species of Dendrobates, and found that genetically it was closer to some small Amazonian poison frogs like D. castaneoticus Caldwell andMyers, 1990 (Lötters 2003), but these authors took a prudent position about this surprising find ("it should be interpreted cautiously until more sequence data for this species become available"), and did not make any nomenclatural changes. Grant et al (2006), based on molecular data only, erected the genus Adelphobates for D. galactonotus, the sympatric, much smaller D. castaneoticus, and two other small species, although from several comments it is clear they realized the discrepancy between the results of molecular and morphological character data ("…the occurrence of galactonotus in this clade is unexpected, as its morphology shares little with the diminutive castaneoticus and quinquevittatus") within this new genus.…”
Section: Introductionmentioning
confidence: 99%